PENGARUH MODEL COOPERATIVE LEARNING TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MENGANALISIS SEJARAH DI SMA NEGERI 4 METRO - Astiana Cahayanti; Elis Setiawati (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The low ability to analyze students can be caused by external factors such as, the model or method used by the teacher is less suitable to the state of students in the classroom and internal factors such as the willingness of students or the interest of students to learn less. Based on the results of pre-survey conducted in SMA Negeri 4 Metro in the academic year 2017/2018 shows that students' analyzing ability in learning is still relatively low. The purpose of this study was to determine the effect of Cooperative Integrated Reading and Compositian Cooperative Learning Model (CIRC) to analyze student ability. Based on data analysis using normality test, homogeneity test, hypothesis test (two equity test average and difference of two mean) where result of pre test in experiment class is sig equal to 0,200 and control class with sig value equal to 0,181. Then it can be concluded that the data obtained more than sig> H0 is accepted, in other words the samples are normally distributed. Then the homogeneity test results that have been done by using One Way Anova that is by getting sig result 0,065. Then it can be concluded that the level of significance> 0.05 receives H0 or in other words both populations have the same or homogeneous variants. Furthermore, based on result of equation test of two sig average get 0,039 <0,05 then H0 is rejected which mean H1 accepted. The conclusion of this research is the influence in using Cooperative Learning Model Type Cooperative Integrated Reading and Compositian (CIRC) Against the ability to analyze history of class X students IPA1 SMA Negeri 4 Metro